Changing the Subject: The Place of Revisions in Grammatical Development. - Rispoli, Matthew (Journal of Speech, Language & Hearing Research, 2018)
Purpose: This article focuses on toddlers' revisions of the sentence subject and tests the hypothesis that subject diversity (i.e., the number of different subjects produced) increases the probability of subject revision. Method: One-hour language samples were collected from 61 children (32 girls) at 27 months. Spontaneously produced, active declarative sentences (ADSs) were analyzed for subject diversity and the presence of subject revision and repetition. The number of different words produced, mean length of utterance, tense/agreement productivity score, and the number of ADSs were also measured. Results: Regression analyses were performed with revision and repetition as the dependent variables. Subject diversity significantly predicted the probability of revision, whereas the number of ADSs predicted the probability of repetition. Conclusion: The results support the hypothesis that subject diversity increases the probability of subject revision. It is proposed that lexical diversity within specific syntactic positions is the primary mechanism whereby revision rates increase with grammatical development. The results underscore the need to differentiate repetition from revision in the classification of disfluencies.